Komunikasi Persuasif Wedding Organizer dalam Menyelenggarakan Event Pernikahan - Alfan Irham Ramadhani; Anne Ratnasari (Bandung Conference Series: Public Relations, 2024)
Abstract. Humans as social creatures depend on communication and language to fulfill their needs and survive, with persuasive communication being an important key, especially for wedding organizers like Megrashy Wedding Planner. In the digital era, social media is effective for building brand awareness. Megrashy Wedding Planner, with its good reputation, unique wedding concept, and artist involvement, uses Instagram and platforms like Bridestory to attract prospective brides and grooms in Bandung. This research aims to analyze the persuasive communication tactics used by wedding organizers at wedding events. To analyze the management of Instagram as a medium for promoting Wedding Organizers in organizing wedding events. To analyze testimonials as an advantage of Wedding Organizer Megrashy Wedding Planner in organizing wedding events. Using a constructivist paradigm, qualitative methods, and a case study approach, this research uses symbolic interactionism theory and triangulation techniques to verify data through observation and interviews. The research results show that Megrashy Wedding Planner is effective in using attractive visual content and personal interactions to attract clients, as well as managing Instagram with a strategy that involves trend research and the use of influencers. Client testimonials are used transparently to build reputation and trust, strengthening Megrashy's position as a trusted wedding organizer. Abstrak. Manusia sebagai makhluk sosial bergantung pada komunikasi dan bahasa untuk memenuhi kebutuhan dan kelangsungan hidup, dengan komunikasi persuasif menjadi kunci penting, terutama bagi wedding organizer seperti Megrashy Wedding Planner. Di era digital, media sosial efektif untuk membangun brand awareness. Megrashy Wedding Planner, dengan reputasi baik, konsep pernikahan unik, dan keterlibatan artis, menggunakan Instagram dan platform seperti Bridestory untuk menarik calon pengantin di Bandung. Penelitian ini bertujuan untuk menganalisis taktik komunikasi persuasif yang dilakukan wedding organizer dalam event pernikahan. Untuk menganalisis pengelolaan Instagram sebagai media untuk mempromosikan Wedding Organizer dalam menyelenggarakan event pernikahan. Untuk menganilisis testimoni menjadi sebuah keunggulan Wedding Organizer Megrashy Wedding Planner dalam menyelenggarakan event pernikahan. Dengan paradigma konstruktivis, metode kualitatif, dan pendekatan studi kasus, penelitian ini menggunakan teori interaksionisme simbolik serta teknik triangulasi untuk verifikasi data melalui observasi dan wawancara. Hasil penelitian menunjukkan Megrashy Wedding Planner efektif menggunakan konten visual menarik dan interaksi personal untuk menarik klien, serta mengelola Instagram dengan strategi yang melibatkan riset tren dan penggunaan influencer. Testimoni klien digunakan secara transparan untuk membangun reputasi dan kepercayaan, memperkuat posisi Megrashy sebagai wedding organizer terpercaya.